Novel data-aided SNR estimation algorithm for QPSK signal in AWGN channel - JIANG Zheng-bo; HONG Wei; LIU Jin; TIAN Ling (Tongxin xuebao)
Novel data-aided SNR estimation algorithm for QPSK signal in AWGN channel was presented.The analytical and simulated results show that the new SNR estimator performs better than ML-DA estimators,especially in the condi-tion of low SNR,it is more precise and more reliable,and is not sensitive to phase errors of the receiver.Finally,the ori-gin of the new estimator’s error was explored and some suggestions were made on its application.